Morphological feature's variability of the watermelon's collectional samples in the film hothouses - З. Д. Сич; І. М. Бобось; І. В. Сидорка (Plant Varieties Studying and Protection)
It was revealed perspective for further selective work and fast-ripening watermelon's varieties such as "Severnoye siyaniye", "Krimson svit", "Gyuj Bao", "Chernogorets", "Kitaiskaya skorospelka", "Borisfen",  "Kahovsky", Linii No 139", "Kitaj No132-4-1" among the watermelon's sample’s collection under conditions of film hothouses. The watermelon’s plants in the film hothouses are more affected by fusarial fading among the diseases. There were revealed the samples such as "Golopristanskij", "Legin", "Foton", "Fabiola", "Kitaj No132-4-1", "Panoniya No 12-Г', which are relatively resistible to that disease. There were selected the fast - ripening and resistible to diseases new heterodyne hybrids F1 51x62 and F1 53x69 of the Dnepropetrovsk Experimental Research Center EOB under the film hothouse’s conditions.